Bioaccumulation of perfluoroalkyl substances in exploited fish and crustaceans: Spatial trends across two estuarine systems. (June 2018) - Taylor, Matthew D.; Beyer-Robson, Janina; Johnson, Daniel D.; Knott, Nathan A.; Bowles, Karl C.
Abstract: Spatial patterns in perfluoroalkyl substances were quantified for exploited fish and crustaceans across two contrasting Australian estuaries (Port Stephens and Hunter River). Perfluorooctane sulfonate (PFOS) was detected in 77% of composites from Port Stephens and 100% of composites from Hunter River. Most species from Port Stephens showed a clear trend with distance to source. In contrast, only a subset of species showed this trend in the Hunter River, potentially due to species movement patterns and differing hydrology. Spatial modelling showed that PFOS concentrations were expected to exceed the relevant trigger value up to 13, 500 m from the main point source for Port Stephens and 9000 m for the Hunter River. These results represent the first major investigation of bioaccumulation of PFASs in exploited species in Australian estuaries, and highlight various factors that can contribute to spatial patterns in bioaccumulation. Highlights: Spatial patterns in PFAS bioaccumulation were quantified in exploited fishes. Some species showed clear trends with distance to source, in some locations. Spatial patterns were likely driven by movement patterns and hydrology.